Mekanisme Tabungan Easy Mudharabah pada PT Bank Syariah Indonesia KCP Medan Tomang Elok - Putri Ismaydina; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to determine the Easy MudharabahSavings Mechanism at PT. Bank Syariah Indonesia KCP MedanTomang Elok. The research method used is descriptive researchusing a qualitative approach. Information obtained from interviews,literature review sourced from journals and critical thinking from theauthor. This interview was conducted for one week. The findings ofthis study are easy mudharabah savings are savings in the form ofsavings that use the Mudharabah muthlaqah principle, namely theresults or profits obtained from the use of funds are divided basedon an agreed ratio. As for the mechanismeasy mudharabah savings made at PT. Bank Syariah Indonesia KCPMedan Tomang Elok, including: opening an easy mudharabahavings account, initial deposit, giving an account book and ATM.